2016
DOI: 10.4236/abb.2016.711042
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of δ-Guaiene, an Aroma Sesquiterpene Compound Accumulated in Agarwood, by Mevalonate Pathway-Engineered <i>Escherichia coli</i> Cells

Abstract: Mevalonate pathway for isoprenoid biosynthesis was constructed in Escherichia coli cells by the transformation with a gene cluster isolated from Streptomyces sp., and farnesyl diphosphate synthase and δ-guaiene synthase genes were coexpressed in this strain. This transformant was capable of liberating an appreciable amount of δ-guaiene, an aroma sesquiterpene compound accumulated in agarwood, and its concentration was elevated to more than 30 μg/ml culture by the incubation with mevalonolactone as an isoprene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Since 2008, Misawa et al have identified several novel Tps genes for the production of volatile sesquiterpenes using recombinant E. coli cells carrying the corresponding unidentified Tps genes derived from edible or flavor plants [2,3,5,6,8,18]. They identified volatile sesquiterpenes produced by E. coli cells that carried the ZzZss2 gene…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2008, Misawa et al have identified several novel Tps genes for the production of volatile sesquiterpenes using recombinant E. coli cells carrying the corresponding unidentified Tps genes derived from edible or flavor plants [2,3,5,6,8,18]. They identified volatile sesquiterpenes produced by E. coli cells that carried the ZzZss2 gene…”
Section: Discussionmentioning
confidence: 99%
“…Functional identification of cryptic terpene synthase (Tps) genes have often been performed using recombinant micro-organisms containing Escherichia coli that can functionally express the corresponding Tps genes and generate the sesquiterpene synthase (TPS) products [1][2][3][4]. In many cases, the generated sesquiterpenes (the TPS products) have been analyzed by gas chromatography-mass spectrometry (GC-MS) using the MS library or co-chromatography with the authentic samples [2,3,[5][6][7][8]. However, such methods are sometimes insufficient for the unambiguous determination of their chemical structures and consequent identification of the Tps genes.…”
mentioning
confidence: 99%
“…In the total ion chromatogram (Figure 3 A), two major peaks were found in the sample released from the transformed tobacco cultures, and they were identified as α-guaiene and δguaiene by the retention indices and mass spectra (Figure 3 B) in the data base, respectively [12,13]. We have previously reported [8,9] that sesquiterpene compounds produced by E. coli cells transformed with GS plus FPS were detected only in the head space of the cultures. The similar situation was also observed in the transformed tobacco BY-2 cells, and α-guaiene and δ-guaiene were found to be accumulated only in the head space of the vials containing the transformed tobacco culture but not in the medium or the cells.…”
mentioning
confidence: 91%
“…More recently, we transformed E. coli with a gene cluster isolated from Streptomyces sp. which contains mevalonate pathway-related genes, and demonstrated [9] that, in this isoprenoid pathway-engineered E. coli, 35 -42 mg δ-guaiene/L culture was accumulated in the presence of appropriate precursors. However, productivity of δ-guaiene in E. coli cell system was not satisfactory, and, therefore, we attempted Figure 2: Schematic presentation of the expression vectors of GS and FPS genes in tobacco BY-2 cell cultures.…”
mentioning
confidence: 93%
See 1 more Smart Citation